2020
DOI: 10.1007/s00221-020-05759-1
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in motor unit firing rates and action potential amplitudes of the first dorsal interosseous during high-, but not low-intensity contractions

Abstract: Despite ample evidence that females are weaker and possess smaller muscle crosssectional areas (CSAs) compared to males, it remains unclear if there are sex-related differences in the properties of motor units (MU). Eleven males (age=22±3 yrs) and twelve females (age=21±1yrs) performed isometric trapezoid muscle actions at 10% and 70% of maximal voluntary contraction (MVC). Surface electromyography signals were recorded and decomposed into MU action potential (AP) waveforms and firing instances. Average MUAP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
27
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 89 publications
3
27
2
Order By: Relevance
“…Although our experimental protocol utilized a slightly greater relative load, this should not have elicited a significant difference in microvascular responses given the similar TTFs. Ultimately, we hypothesized that sex differences in muscle fiber type (Roepstorff et al 2006 ; Haizlip et al 2015 ), and consequentially motor unit activation strategies (Parra et al 2020 ), prompted the markedly different rates of desaturation during the fatiguing exercise. It was interesting that despite the sex difference in rate of decline in StO 2 , there was not a difference in TTF.…”
Section: Discussionmentioning
confidence: 99%
“…Although our experimental protocol utilized a slightly greater relative load, this should not have elicited a significant difference in microvascular responses given the similar TTFs. Ultimately, we hypothesized that sex differences in muscle fiber type (Roepstorff et al 2006 ; Haizlip et al 2015 ), and consequentially motor unit activation strategies (Parra et al 2020 ), prompted the markedly different rates of desaturation during the fatiguing exercise. It was interesting that despite the sex difference in rate of decline in StO 2 , there was not a difference in TTF.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, we hypothesize that some degree of excitation coupling was impaired via by-products such as inorganic phosphate (19), but because of the blockage of venous outward flow, the by-products continued to accumulate triggering greater increases in muscle excitation (20) during subsequent sets until a maximum increase was reached. It is still curious that there were no sex-specific EMG AMP responses considering that men and women may exhibit morphological differences that could affect fatigue processes including substrate utilization, metabolite buildup, and muscle excitability (14,23,54,55). Alternatively, our findings corroborated the notion that cuff pressure does not result in EMG AMP differences as long as venous return is uniformly occluded during largely anaerobic tasks like resistance exercise (9,17,20,49,56).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, of even greater priority than determining the most ideal cuff pressure, there is currently a severe underrepresentation of women in biomedical research, including BFR investigations (12). Counts and coauthors (12) stated that only 29% of acute BFR research participants were women, which is concerning because of the little that is currently known regarding how the BFR stimulus influences female-related exercise responses, whereas there are known sex differences in muscle morphology, function, and plasticity including differences in gene expression after acute resistance exercise (13,14). Unfortunately, despite the repeated calls to increase the number of women in related studies, there is no evidence to suggest that parity has been reached between men and women.…”
mentioning
confidence: 99%
“…In recent years, studies that have included an adequate number of females have demonstrated sex differences in several MU discharge properties, but the results vary across different tasks and conditions. The consensus is that MU discharge (English & Widmer, 2003; Harwood et al ., 2014; Peng et al ., 2018; Parra et al ., 2020; Inglis & Gabriel, 2020; Nishikawa et al ., 2022) and neuromuscular fatigue (Hunter & Enoka, 2001; Celichowski & Drzymała, 2006; Ansdell et al ., 2019; Inglis & Gabriel, 2021; Augsburger et al ., 2022) differ between the sexes (Lulic-Kuryllo & Inglis, 2022). Recent data suggest that females use different recruitment strategies than males at relatively low efforts due to smaller MU size and higher discharge rates (Guo et al ., 2022) but the specific mechanisms underlying these differences remain unknown.…”
Section: Introductionmentioning
confidence: 99%